How Often is Microcarcinoma Thyroid Found in Non-Neoplastic Thyroidectomy Specimen? Eight Years of Experience in an Indonesian Academic Hospital - Fauziah, Dyah; Kurniasari, Nila; Agustin, Leonita (Indonesian Journal of Cancer, 2024)
Background: Papillary thyroid microcarcinoma (PTmC) is a subtype of papillary thyroid carcinoma characterized by a tumor that is no larger than 10 mm. This tumor is frequently discovered by accident during autopsies or in thyroidectomy specimens for other thyroid disorders. This study was conducted to ascertain the incidence of incidental PTmC in thyroidectomy specimens and analyze the clinicopathological characteristics.Methods: A descriptive cross-sectional study design was used. Pathology archives of thyroidectomy specimens between 2012 and 2019 in a single institution were collected. Cases with fine-needle aspiration biopsy (FNAB) before surgery were also studied. The clinical information was retrieved from medical records. Results: 1459 patients underwent thyroid surgery. The clinical diagnosis in 706 cases was neoplasm and in 753 cases was non-neoplasm. There were 697 cases of malignant thyroid tumors. Forty-two cases of papillary thyroid microcarcinoma were found, with 85.71% affected females, with the male-to-female ratio was 1:6. The majority of PTmC were clinically diagnosed as benign lesions with multinodular goiter as the most common diagnosis. Fine needle aspiration biopsies were performed on 18 patients. There were 2 cases found in laryngectomy specimens for laryngeal cancer. There were 2 cases presented initially as metastasis nodules in lymph nodes and the lung, respectively.Conclusions: PTmC comprises 6.03% of all malignant thyroid neoplasms and is mainly found incidentally in thyroidectomy specimens for benign thyroid lesions with clinical diagnosis as multinodular goiter. The male-to-female ratio is 1:6. Regional and distant metastasis are not common in PTmC.